(untitled) (Sains Humanika, 2016)
The obligation to pay income zakat has a significant effect on increasing the total collection of income zakat in Kelantan. Income zakat here refers to zakat that is liable on earnings that include emoluments and other forms of income. The Kelantan Islamic Religion and Malay Customs Council (MAIK) made this mandatory in Kelantan on 16 March 1999. The creation of this fatwa (religious decree) had inadvertently affected the increase in total collection of income zakat in Kelantan. For example, from 2001 to 2013, the percentage of zakat collected had increased to 18.55%, from 5.98%. The question is, what are the factors that influence the compliance by the muzakki to pay income zakat at MAIK? This qualitative study used primary and secondary data. The primary data was obtained by distributing questionnaires to respondents, whereas the secondary data was obtained from previous studies and literature reviews related to the compliance to pay income zakat. All the data were analysed using the content analysis method. Lastly, this study found that the factors that influenced the muzakki compliance to pay income zakat at MAIK were factors such as the level of satisfaction, needs of the state, attitude towards the state, facilities, confidence and quality of service.Â